Practical works of the late Reverend Alexander Moncrieff ... with two treatises ... - Moncrieff, Alexander (Puritan collection of English and American literature, 1779)
In defence of the Supreme Deity of the Son of God. -- An enquiry into the principle and end of moral actions.